Bounds on the constrained capacity for the diffusive poisson molecular channel with memory - Ratti, Francesca; Vakilipoor Takaloo, Fardad; Awan, Hamdan; Magarini, Maurizio (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
This letter focuses on the analysis of a diffusion-based molecular communication (MC) system where the received signal is approximated as a Poisson random variable. Concentration shift keying (CSK) is used as the modulation technique for encoding information in the system. In particular, this work aims to study the performance of the MC system in terms of reliable information exchange for the channel with finite-state memory, which introduces intersymbol interference (ISI). The main objective is the derivation of analytical expressions for the upper and the lower bound of the constrained channel capacity for a range of values of the modulated symbols, i.e., for a number of different sets of amplitude levels of CSK modulation, and for various levels of ISI. In addition, the numerical evaluation of the derived expressions is presented. Results allow discussing the relationship between ISI level and achievable channel capacity. Moreover, numerical outcomes highlight how the estimation of the bounds is not affected by the presence of ISI in the case of binary CSK modulation, as the bounds remain quite tight.
Created from Fastlane, Scopus look-up
Keywords: Channel capacity; Intersymbol interference; Molecular communication; Mutual information